Abnormal prostate microbiota composition is associated with experimental autoimmune prostatitis complicated with depression in rats - Liu, Feng; Xu, Xiaolin; Wang, Zhong; Wu, Peng (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Microbiota play essential roles in the pathogenesis of prostatitis and depression. However, the changes in prostate microbiota have not yet been explored in rats with prostatitis/depression. This study aimed to investigate the changes of prostate microbiota in rats with prostatitis/depression. Methods: Rats with experimental autoimmune prostatitis (EAP) complicated with depression were constructed through injection of rat prostate antigen with immunoadjuvants followed by application of chronic unpredictable mild stress (CUMS). The rats were subjected to inflammatory factor detection and behavioral testing to confirm the establishment of the model. Subsequently, the prostate microbiota was assayed in the rats and compared by 16S rRNA gene sequencing. Results: A rat model of EAP complicated with depression was established and confirmed by increases in IL-1β, IL-6, and TNF-α as well as the occurrence of depressive‐like behaviors. EAP/CUMS significantly altered the richness, evenness, and composition of prostate microbiota. Forty-six taxonomic biomarkers for prostate microbiota were enriched in rats with EAP/depression and exhibited statistically significant and biologically consistent differences. Metabolomics profiling revealed that EAP/depression was associated with reductive acetyl coenzyme A pathway, L-lysine fermentation to acetate and butanoate, protein N-glycosylation and purine nucleobases degradation I, which is regulated by DCE29, Nocardioes, Helicobacter and Dorea. Conclusion: Findings from the study demonstrate the existence of abnormal prostate microbiota in EAP complicated with depression and may be helpful in the treatment of comorbid diseases of prostatitis and depression.